Case Report: Recognition of Devastating Primary Amoebic Meningoencephalitis (PAM) Caused by Naegleria fowleri: Another Case in South China Detected via Metagenomics Next-Generation Sequencing Combined With Microscopy and a Review - Chen, Shenggen; Che, Chunhui; Lin, Wanhui; Chen, Baojian; Huang, Xinming; Liu, Changyun; Huang, Huapin (Frontiers in Tropical Diseases, 2022)
Introduction Primary amoebic meningoencephalitis (PAM) caused by Naegleria fowleri is seldom reported in mainland China. Methods One case from South China was presented, and the clinical features of the PAM, especially the early CT features, were compared to those in the literatures from PubMed/Web of Science/China National Knowledge internet (CNKI). Case Presentation and Results A 47-year-old man with a high fever came to the fever clinic. Twelve hours later, the man lost consciousness and exhibited generalized tonic-clonic seizures and needed ventilator-controlled ventilation. Then, he was admitted to the neurology intensive care unit (NICU). The opening pressure of his cerebrospinal fluid (CSF) was over 500 mm H2O with highly increased leukocyte/protein levels and very low glucose levels. Three days after admission, high copy numbers of Naegleria fowleri amoebae were detected by metagenomics next-generation sequencing (mNGS) and cysts were visible with wet mount microscopy. Four days after admission, the patient experienced brain death. However, the relatives of the patient did not want to give up, and he received amphotericin B (AmB). During hospitalization, he suffered from severe damage to the liver and kidneys and electrolyte disorders that required continuous renal replacement therapy (CRRT). Review All 20 included PAM patients suffered from fever. Seventeen of them had headache and neck stiffness. Ten of them showed generalized brain edema. To date, 7 cases of PAM have been reported in China. Only one patient survived. Most of the patients showed generalized brain edema. Only the surviving patient showed focal edema. He died three months later. Conclusion Rapidly progressive meningoencephalitis in which the CSF results are similar to those suffered from a bacterial infection should be considered a possible case of PAM. It can be rapidly detected with microscopy in CSF wet mounts but needs further molecular investigation for confirmation, and mNGS should be a new method used for rapid and precise identification. Moreover, CRRT may prolong the survival time of PAM patients with multiple organ failure.